PENGARUH PENDIDIKAN MORAL DALAM KELUARGA DAN DISIPLIN BELAJAR DI SEKOLAH TERHADAP HASIL BELAJAR EKONOMI - Chyci Pramitha; Darwin Bangun; Nurdin Nurdin (FKIP Unila, 2013)
Learning outcomes is the result obtained after attending diwujutkan learning activities in the form of scores or numbers after following the test of the learning process. To achieve optimal learning results, students should explore the potential that comes from within and outside the student, such as moral education in the family and school discipline. Based on preliminary research conducted in MA Sadar Sriwijaya note that overall student learning outcomes on economic subjects is low. The purpose of this study was to obtain the data and find a positive effect of moral education in the family and school discipline learning outcomes economy class X MA Sadar Sriwijaya East Lampung school year 2012/2013. This study population is students of class X MA Sadar Sriwijaya much as two classes by the total number of students 84 students. The sampling technique is simple random sampling is by using the formula T. Yamane obtained by 69 students. The method used is descriptive verification by using the ex post facto and surveys. The results showed that, there is the influence of moral education in the family and school discipline learning outcomes economy class X MA Sadar Sriwijaya East Lampung school year 2012/2013. Based on the analysis of data obtained 31.654 F count F table 3.98 indicated by multiple linear regression with the coefficient of determination (r2) 0.490 which means that the learning outcomes are influenced by moral education in the family and school discipline by 49.0% and the remaining 51, 0% dipengaurhi by other factors.